Need for Action and Reform Options After the Federal Election - ZG Überblick (Wirtschaftsdienst)
Abstract On the occasion of the federal election on 26 September 2021, this Zeitgespräch is dedicated to the challenges for the future federal government. The range of topics is as diverse as the parties’ ideas. In addition to discussing the topics of digitalisation, decarbonisation, and education and training of skilled workers, the contributions also focus on financial policy. Equality also plays a central role, often neglected in the election campaign. What steps should the next federal government take to meet the challenges ahead? The differences in the election programmes of the FDP and the Greens as well as possible lines of compromise are discussed. Finally, the contributions consider which measures should be taken to increase productivity in order to shape the structural change — caused by digitalisation and the energy transition.